COVID-19 induced psychosocial challenges in South African higher education: Experiences of staff and students at two rural universities - Babawande Emmanuel Olawale; Bonginkosi Hardy Mutongoza; Emmanuel Olusola Adu; Bunmi Isaiah Omodan (Research in Social Sciences and Technology, 2021)
Although the global impact of the COVID-19 pandemic on the education and mental health of the university environment is relatively unknown, it is expected to be very significant considering the high incidence of emotional reactions amongst university students and staff. While fears around COVID-19 exposure, anxieties, and the challenges of support normalize stress, anxiety, and depression as emotional reactions in the face of the pandemic, this psychosocial impact has negative consequences for the university community. Thus, in order to salvage the higher education institutions from the debilitating effects of the pandemic, there is a clear need to safeguard the welfare of students and staff. Hence, it becomes vital to examine the experience of members of the university community during the COVID-19 crisis in order to develop measures and implement interventions that will assist in navigating psychosocial challenges. To achieve this objective, the study employed a mixed-method research approach in which data was collected using web-based survey and online interviews. Concurrent triangulation sampling technique was employed to select a sample of fifteen (15) students, five (5) university managers, and five (5) lecturers – making twenty-five (25) respondents at each of the two universities, thus making a cumulative total of fifty (50) at two (2) rural universities in the Eastern Cape Province, South Africa. Thus, qualitative and quantitative data collected were analysed concurrently by first reporting the qualitative findings and then comparing them to the quantitative findings. Findings revealed that although the university environment traditionally provided opportunities for strengthening social ties which satisfy the universal need to belong to a community, the COVID-19 pandemic has altered rural university life, thus, significantly impacting on psychosocial wellbeing. The study recommends that rural institutions must facilitate psychosocial wellness programming with the assistance of wider stakeholders such as the government and the private sector who can assist in financing this initiative.